Factors That Affect The Nonpayment Of Municipal Services In Madibeng, Mamelodi And Soshanguve Townships Of South Africa - Worku, Zeleke (Journal of Applied Business Research, 2017)
The study was conducted in Madibeng, Mamelodi and Soshanguve townships of South Africa in order to assess and evaluate the main reasons for the non-payment of municipal services by members of the community. The study was conducted based on a stratified random sample of size 428 households. Statistical data analyses were performed by using methods such as ordered logistic regression analysis and Bayesian analyses. The results showed that 22% of households in Madibeng, 54% of households in Mamelodi and 78% of households in Soshanguve were willing to pay for municipal services that were provided to them by their local municipalities. Reluctance to pay for municipal services was significantly influenced by employment status, level of formal education and race group.